Reliability and validity of an indoor local positioning system for measuring external load in ice hockey players - Gamble, A. S.; Bigg, J. L.; Pignanelli, C.; Nyman, D. L.; Burr, J. F.; Spriet, L. L. (European Journal of Sport Science, 2023)
This study determined the reliability and validity of a Kinexon local positioning system (LPS) for measuring external load in ice hockey players during an on-ice session. Fourteen ice hockey players (25.1 y, 78.6 kg, 176.9 cm) wore two LPS sensors to examine the inter-sensor reliability of the LPS during an on-ice session, and LPS speed and acceleration were measured during 40 m linear on-ice sprints and compared to a previously validated robotic sprint device to examine LPS accuracy. The coefficient of variation (CV), standard error of measurement (SEM), and intra-class correlation coefficient (ICC) were calculated for each LPS measure. Pearson`s correlations, simple linear regressions, and Bland-Altman plots were used to test the agreement and relationship between the two systems. Statistical significance was determined at p < 0.05. The majority of LPS measures were reliable (CV < 10% and ICC > 0.9) when comparing the two sensors worn by each player. Peak speed, speed at 5 m, and 0-5 m acceleration were all comparable to those reported by the robotic sprint device, with nearly perfect (peak speed and 0-5 m acceleration) and very large (speed at 5 m) magnitudes of correlation and mean biases <0.5 km/hr for speed measures and <0.01 m/s2 for acceleration. The present results demonstrate that the Kinexon LPS is reliable and accurate for investigating on-ice external load in ice hockey players when sensors are consistently secured on the back of the players` shoulder pads.